2021
DOI: 10.1016/j.compfluid.2020.104816
|View full text |Cite
|
Sign up to set email alerts
|

On the generation of turbulent inflow for hybrid RANS/LES jet flow simulations

Abstract: The present work is devoted to the assessment of a low-noise turbulence generation methodology used to produce boundary layer with three-dimensional resolved turbulence at the exit of a jet nozzle to reproduce experimental conditions. The method relies on the use of roughness elements introduced in the computational domain with Immersed Boundary Conditions and ZDES mode 3 (Wall Modelled LES branch of ZDES). The simulation of a round jet at M=0.9 and Reynold number 10 6 with turbulence generation is compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Surprisingly, we can observe how the adaptive simulation hpG2 seems to provide closer results to the experiment, while the more refined hpG3 mesh overestimates the length of the potential core. Even though this results could seem unexpected, this behaviour has been already pointed out by Shur et al in [65] (in orange lines), and can be found in results from Brès et al [62] (in green lines) and Gand et al [63] (in magenta lines) as well. The trend is clear, even though for Shur and Gand this is more marked than for Brès.…”
Section: Quantitative Data Analysissupporting
confidence: 67%
See 2 more Smart Citations
“…Surprisingly, we can observe how the adaptive simulation hpG2 seems to provide closer results to the experiment, while the more refined hpG3 mesh overestimates the length of the potential core. Even though this results could seem unexpected, this behaviour has been already pointed out by Shur et al in [65] (in orange lines), and can be found in results from Brès et al [62] (in green lines) and Gand et al [63] (in magenta lines) as well. The trend is clear, even though for Shur and Gand this is more marked than for Brès.…”
Section: Quantitative Data Analysissupporting
confidence: 67%
“…The nozzle test case analysed in this work corresponds to the configuration described in [62], for which experiments have been performed at the Bruit & Vent jet-noise facility of the Institut PPRIME, Poitiers, France, with reference data available. Numerical results are available as well in the literature: this configuration has been simulated with LES by Brès et al [62] to analyse features as near-wall adaptive mesh refinement, synthetic turbulence and wall modelling inside the nozzle in LES, with hybrid RANS/LES by Gand et al in [63] to assess the generation of a turbulent inflow and with RANS by Neifeld et al [64] for jet noise prediction purposes with eddy relaxation source model.…”
Section: Mesh Sensitivity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This configuration has been simulated using LES by Brès et al [82] to analyse features as near-wall adaptive mesh refinement, synthetic turbulence and wall modelling inside the nozzle. Hybrid RANS/LES simulations have been performed by Gand et al in [83] to assess the generation of a turbulent inflow, and RANS simulations by Neifeld et al [84] for jet noise prediction purposes with an eddy relaxation source model.…”
Section: Laminar Flow Past a Delta Wing At Low Reynolds Number And High Angle Of Attackmentioning
confidence: 99%
“…We appraise the above adaptive remeshing strategy in the physical context described in [22], for which experimental and numerical data are available in the literature, see also [57] and [79] for further investigations aimed at predicting turbulence generation and jet noise.…”
Section: Numerical Example: Simulation Of the Subsonic Turbulent Nozz...mentioning
confidence: 99%